2019
DOI: 10.1074/jbc.ra119.008837
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologically diverse antidepressants facilitate TRKB receptor activation by disrupting its interaction with the endocytic adaptor complex AP-2

Abstract: Antidepressant drugs activate TRKB (tropomyosin-related kinase B), however it remains unclear whether these compounds employ a common mechanism for achieving this effect. We found by using mass spectrometry that the interaction of several proteins with TRKB was disrupted in the hippocampus of fluoxetine-treated animals (single intraperitoneal injection), including members of the AP-2 complex (adaptor protein complex-2) involved in vesicular endocytosis. The interaction of TRKB with the cargo-docking mu subunit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 67 publications
(81 reference statements)
2
55
0
Order By: Relevance
“…These data indicate that PTPσ interacts with TRKB. Furthermore, our previous proteomic study found PTPσ among the proteins that were immunoprecipitated with TRKB in hippocampal samples of the adult mouse brain ( Fred et al, 2019 ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…These data indicate that PTPσ interacts with TRKB. Furthermore, our previous proteomic study found PTPσ among the proteins that were immunoprecipitated with TRKB in hippocampal samples of the adult mouse brain ( Fred et al, 2019 ).…”
Section: Resultsmentioning
confidence: 97%
“…Cell-surface ELISA was conducted to assess PTPσ levels found on the cell surface as previously described ( Zheng et al, 2008 ; Fred et al, 2019 ). Briefly, cortical cells were cultivated in clear-bottom 96-well plates (ViewPlate 96, PerkinElmer).…”
Section: Methodsmentioning
confidence: 99%
“…Simulations predict that membrane lipids also participate in fluoxetine binding to TRKB. As TRKB exists as a multi-protein complex that also includes transmembrane proteins 66,67 , it is possible that other proteins and lipids participate in antidepressant binding to TRKB in cell-type and subcellular compartment dependent manner. Further characterization of this binding site may yield important information for discovery of new antidepressants with increased potency for plasticity-related behavioral effects.…”
Section: Discussionmentioning
confidence: 99%
“…Typical monoaminergic antidepressants are reported to rapidly increase the phosphorylation of TrkB, which has been used as a surrogate marker for increased BDNF activity (Saarelainen et al, 2003). However, recent studies demonstrate that these monoaminergic antidepressants rapidly activate TrkB receptors via interactions with other regulatory sites on the receptor, including the endocytic adaptor complex AP-2 (Fred et al, 2019) and a cholesterol regulatory site (Casarotto et al, 2019) that are independent of BDNF release. Importantly, the rapid effects of monoaminergic antidepressants on TrkB do not correspond with the time lag for the therapeutic response to these agents, and there is no direct evidence that these agents produce activity-dependent synaptic effects.…”
Section: Acting Antidepressants Increase Bdnf Releasementioning
confidence: 99%